The Oxford handbook of the Cold War - Immerman, Richard H. 1949- HerausgeberIn; Goedde, Petra 1964- HerausgeberIn (Oxford University Press, 2013)
34 essays by a team of leading scholars offering a broad reassessment of the Cold War, calling into question orthodox ways of ordering the chronology of the period and presenting new insights into the global dimension of the conflict